Localization of interferons and interleukin 2 in polymyositis and muscular dystrophy. - Isenberg, D; Rowe, D; Shearer, M; Novick, D; Beverley, P (1986)
Muscle biopsies from nine patients with polymyositis, six with muscular dystrophy, six with other muscle diseases and three controls have been studied with a panel of 10 monoclonal antibodies (MoAb) identifying T lymphocytes, HLA-class I antigens, alpha, beta and gamma interferons and interleukin 2 (IL-2). The result confirm that the staining of the sarcolemma with anti-HLA class I antibody is weak or negative, except in areas adjacent to infiltrating leucocytes or where muscle fibre damage is evident. The very similar tissue distribution of alpha, beta and gamma interferons in the polymyositis biopsies supports the hypothesis that interferons are released by the inflammatory infiltrate and induce the class I antigen expression. In contrast, little interferon was demonstrated in the dystrophic muscle implying that class I expression in these disorders must occur by a different mechanism. Little IL-2 was demonstrated in any of the biopsies though some unexplained small dense accumulations were identified by one of the anti IL-2 MoAb.